The Role of Muhammadiyah Mosques in Forming Harmonious Families Through Islamic Education in Gresik Regency - Noor Amirudin; Suyoto Suyoto (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
This study aims to analyze the implementation of Islamic religious education in the formation of sakinah families at Masjid Ahmad Dahlan and to determine the outcomes of its implementation on the development of congregational families. This research employed an empirical study with a qualitative approach. Data collection techniques included interviews, observations, and documentation, while the data were analyzed using descriptive analysis methods. The findings indicate that the development of sakinah families through Islamic religious education at Masjid Ahmad Dahlan includes the fulfillment of social, spiritual, and material needs. The guidance activities have created a harmonious social pattern that supports the formation of sakinah families. Furthermore, the results show an improvement in the spiritual aspects of the congregation, indicated by the fulfillment of both material and spiritual needs as characteristics of a sakinah family. Therefore, the implementation of Islamic religious education at Masjid Ahmad Dahlan contributes positively to the formation of sakinah families, although it has not yet reached the highest level of sakinah.